Tumor vascular endothelial cells promote immune escape by upregulating PD-L1 expression via crosstalk between NF-κB and STAT3 signaling pathways in nasopharyngeal carcinoma - Yan Wang; Yuanyuan Chen; Yuanyuan Liu; Jingjing Zhao; Gongming Wang; Hao Chen; Yan Tang; Dijun Ouyang; Songzuo Xie; Jinqi You; Xinyi Yang; Minxing Li; et al. (Cell Death and Disease)
Abstract Aberrant vascular systems are significant indicators of cancer and play pivotal roles in tumor immunomodulation. However, the role of PD-L1 expressed on vascular endothelial cells (VECs) in the tumor immune microenvironment of nasopharyngeal carcinoma (NPC), as well as its correlation with patient prognosis, remains unclear. According to in vitro experiments conducted in our research, NPC tumor supernatants could upregulate PD-L1 expression on HUVECs, and the upregulated PD-L1 could bind to PD-1 on T cells leading to diminished T cell killing. The results of animal experiments similarly showed that elevated levels of PD-L1 on tumor VECs hindered the anti-tumor effectiveness of T cells, resulting in immune evasion and tumor progression. Furthermore, PD-L1 expression on tumor VECs served as a valuable prognostic marker, with heightened expression linked to poorer prognosis in NPC patients. Mechanistically, we discovered that the interaction between NF-κB and STAT3 signaling pathways may contribute significantly to the up-regulation of PD-L1 on VECs in NPC. Together, our work provides novel insights into identifying prognostic markers and strategies for reversing immune evasion mechanisms in NPC.